E-filing Asset Declarations : Benefits and Challenges - Kotlyar, Dmytro; Pop, Laura (World Bank, Washington, DC, 2019)
StAR—the Stolen Asset Recovery Initiative—is a partnership between the World Bank Group and the United Nations Office on Drugs and Crime (UNODC) that supports international efforts to end safe havens for corrupt funds. This paper presents an overview of the benefits and challenges associated with transitioning from paper-based to electronic filing. While many of the experiences and practices presented can be relevant to experts from countries across all regions and income levels, the primary audience is policymakers, asset declaration/anti-corruption experts, and practitioners in middle-income countries, with a focus on countries in Europe and Central Asia. This paper provides an overview of the topic and does not aim to discuss all technical issues exhaustively.